Komunikasi Verbal dan Nonverbal Dalam Penjualan Produk Dana Usaha Organisasi Mahasiswa Fakultas Ilmu Administrasi Universitas Brawijaya - Fara Ika Aulia; Nurul Pringgowati; Arsih Amalia Chandra Permata (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
This research discusses the role of verbal and nonverbal communication in selling student organization's danus products. Student organizations often hold danus sales activities to raise funds. The success of the danus sales depends on the sellers' ability to communicate with potential buyers. This study aims to identify the role of verbal and nonverbal communication in achieving successful sales of business funds by student organizations. The research method applied was qualitative, with data collection techniques involving observation and interviews. The results showed that verbal and nonverbal communication played an important role in the process of selling business fund products by student organizations of the Faculty of Administrative Sciences. Verbal communication becomes the main means to explain product features in detail, offer the benefits that the product has, and provide clear and informative responses to buyers' questions. Meanwhile, nonverbal communication, through friendly facial expressions, eye contact, and body movements that show confidence, plays a role in reinforcing messages and building positive relationships with buyers.